Coaxial electrospinning of liquid crystal-containing poly(vinylpyrrolidone) microfibres - Enz, Eva; Baumeister, Ute; Lagerwall, Jan (Beilstein Journal of Organic Chemistry, 2009)
With the relatively new technique of coaxial electrospinning, composite fibres of poly(vinylpyrrolidone) with the liquid crystal 4-cyano-4′-octylbiphenyl in its smectic phase as core material could be produced. The encapsulation leads to remarkable confinement effects on the liquid crystal, inducing changes in its phase sequence. We conducted a series of experiments to determine the effect of varying the relative flow rates of inner and outer fluid as well as of the applied voltage during electrospinning on these composite fibres. From X-ray diffraction patterns of oriented fibres we could also establish the orientation of the liquid crystal molecules to be parallel to the fibre axis, a result unexpected when considering the viscosity anisotropy of the liquid crystal kept in its smectic phase during electrospinning.
Keywords: coaxial electrospinning; composite material; core-sheath fibres; liquid crystal; smectic phase

US Patent - Cooley, J. F. (1902)

US Patent - Morton, W. J. (1902)

(untitled) - Li, D.; Xia, Y. N. (Adv. Mater., 2004)

(untitled) - Burger, C.; Hsiao, B. S.; Chu, B. (Annu. Rev. Mater. Res., 2006)

(untitled) - Reneker, D. H.; Yarin, A. L. (Polymer, 2008)

(untitled) - Greiner, A.; Wendorff, J. H. (Adv. Polym. Sci., 2008)

(untitled) - Rutledge, G. C.; Fridrikh, S. V. (Adv. Drug Delivery Rev., 2007)

(untitled) - Li, D.; Wang, Y.; Xia, Y. (Nano Lett., 2003)

(untitled) - Teo, W. E.; Ramakrishna, S. (Nanotechnology, 2006)

(untitled) - Sun, Z.; Zussman, E.; Yarin, A. L.; Wendorff, J. H.; Greiner, A. (Adv. Mater., 2003)

(untitled) - Loscertales, I. G.; Barrero, A.; Márquez, M.; Spretz, R.; Velarde-Ortiz, R.; Larsen, G. (J. Am. Chem. Soc., 2004)

(untitled) - Li, D.; Xia, Y. (Nano Lett., 2004)

(untitled) - Lagerwall, J. P. F.; McCann, J. T.; Formo, E.; Scalia, G.; Xia, Y. (Chem. Commun., 2008)

(untitled) - Cordoyiannis, G.; Zidansek, A.; Lahajnar, G.; Kutnjak, Z.; Amenitsch, H.; Nounesis, G.; Kralj, S. (Phys. Rev. E, 2009)

(untitled) - Hu, Y.; Huang, Z. M. (J. Appl. Phys., 2007)

(untitled) - Gray, G. W.; Lydon, J. E. (Nature, 1974)

(untitled) - Urban, S.; Przedmojski, J.; Czub, J. (Liq. Cryst., 2005)

(untitled) - Safinya, C. R.; Sirota, E. B.; Plano, R. J. (Phys. Rev. Lett., 1991)

(untitled) - Hamley, I. W.; Castelletto, V.; Parras, P. (Phys. Rev. E, 2006)